2011
DOI: 10.1210/jc.2010-2098
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Room Light before Bedtime Suppresses Melatonin Onset and Shortens Melatonin Duration in Humans

Abstract: These findings indicate that room light exerts a profound suppressive effect on melatonin levels and shortens the body's internal representation of night duration. Hence, chronically exposing oneself to electrical lighting in the late evening disrupts melatonin signaling and could therefore potentially impact sleep, thermoregulation, blood pressure, and glucose homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
197
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(225 citation statements)
references
References 50 publications
7
197
3
2
Order By: Relevance
“…In the PVT, with preceding DL exposure, reaction times in the morning were faster under MBL than under CTRL. These results indicate a sensitization effect of prior (low) light history, similar to the effects on melatonin suppression [21], subjective sleepiness, and melatonin secretion during the night [23,34]. Such a physiological light “sensitization” effect takes place when exposure to low-intensity light leads to a stronger response during a subsequent exposure.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the PVT, with preceding DL exposure, reaction times in the morning were faster under MBL than under CTRL. These results indicate a sensitization effect of prior (low) light history, similar to the effects on melatonin suppression [21], subjective sleepiness, and melatonin secretion during the night [23,34]. Such a physiological light “sensitization” effect takes place when exposure to low-intensity light leads to a stronger response during a subsequent exposure.…”
Section: Discussionmentioning
confidence: 61%
“…Melanopic light effects comprise a variety of physiological and behavioral functions, and they vary with time of day, previous light history, exposure duration, and the spectral composition of light [13,14,15,16,17,18]. The effects of light history lead to stronger or weaker effects in response to light on the same or the next day, demonstrated by melatonin secretion, subjective alertness, and cognitive performance [19,20,21,22,23]. Nowadays, different light-emitting electronic devices are widely used (late) in the evenings, and this affects subjective sleepiness, cognitive performance, sleep, and alertness the next morning [8,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The circulating levels of both display robust diurnal patterns (Migeon et al 1956, Ralph et al 1971. Using the CR and FD experimental protocols, the secretion rhythms of cortisol (el-Hajj Fuleihan et al 1997, Wehr et al 2001, Aeschbach et al 2003, Scheer et al 2010) and melatonin (Dijk et al 1999, Wehr et al 2001, Cain et al 2010, Gooley et al 2011 have been shown to be under direct regulation by the circadian clock. Not surprisingly, both hormones also act as major hormonal output pathways that propagate the time signal from the SCN to various other tissues.…”
Section: Endocrine Rhythms: Clock Vs Behavioral Regulationmentioning
confidence: 99%
“…Secretion of melatonin exhibits circadian rhythms and is suppressed by bright light (Burgess et al, 2001;Kubota, 2002). Even room lights such as fluorescent lamps can attenuate melatonin excretion duration at night (Harada, 2004;Gooley et al, 2011). This evening lights might include lights with high color temperature from the monitor of PC, TV-game, and mobile phone.…”
Section: Melatonin Synthesis From Serotonin Can Be Suppressed By Evenmentioning
confidence: 99%